Ubiquitous computing and ambient intelligence : sensing, processing, and using environmental information : 9th International Conference, UCAmI 2015, Puerto Varas, Chile, December 1-4, 2015, Proceedings /: sensing, processing, and using environmental information : 9th International Conference, UCAmI 2015, Puerto Varas, Chile, December 1-4, 2015, Proceedings. (2015) - Unknown
No abstract available